(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this dissertation was to investigate the impact of personality on women workingin the industrial sector in Ajmer (Rajasthan). As a result, the personality qualities of neuroticism,extraversion, conscientiousness, openness to experience, and agreeableness were examined in this studyas predictors of job success. Because there are few studies on women’s career happiness in non-westerncontexts, particularly in Rajasthan, this research can better comprehend the impact of w omen’scharacteristics on the manufacturing business. The study used an English-language structuredquestionnaire. A total of 50 middle management respondents took part in the study. This study adds tothe body of knowledge in the field of women’s personality and offers recommendations for themanufacturing business.